2003
DOI: 10.1172/jci18193
|View full text |Cite
|
Sign up to set email alerts
|

Antithetic regulation by β-adrenergic receptors of Gq receptor signaling via phospholipase C underlies the airway β-agonist paradox

Abstract: subtype 3 receptor (M3R); thromboxane A2 receptor (TXA2R); 5-hydroxytryptamine subtype 2 receptor (5-HT2R); phospholipase C (PLC); inositol 1,4,5 trisphosphate (IP3); enhanced pause (Penh); airway resistance (Raw); relative units (RUs); 125 I-cyanopindolol ( 125 I-CYP); β2AR overexpression (β2AR-OE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 26 publications
4
72
0
4
Order By: Relevance
“…LTB 4 , like a number of other arachidonic acid metabolites, is increased in inflammatory states such as asthma, with elevated local levels in the airway (20). The high-affinity receptor for LTB 4 , LTB4R, is well recognized as being expressed on neutrophils and other leukocytes (eosinophils, T-lymphocytes) and, when activated by its endogenous agonist, promotes leukocyte migration to the lung and participates in activation and degranulation (21). To our knowledge, LTB4R expression on human ASM cells has not been previously identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LTB 4 , like a number of other arachidonic acid metabolites, is increased in inflammatory states such as asthma, with elevated local levels in the airway (20). The high-affinity receptor for LTB 4 , LTB4R, is well recognized as being expressed on neutrophils and other leukocytes (eosinophils, T-lymphocytes) and, when activated by its endogenous agonist, promotes leukocyte migration to the lung and participates in activation and degranulation (21). To our knowledge, LTB4R expression on human ASM cells has not been previously identified.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports, though, have shown significant contraction of lung parenchymal strips by nanomolar concentrations of LTB 4 (24). Some studies have concluded that LTB 4 antagonists have minor effects on leukocyte accumulation but decrease bronchial hyperreactivity (25,26), another showed decreased leukocyte recruitment but no effect on pulmonary function (27), and another found that antigen-induced bronchoconstriction was decreased but eosinophil accumulation and acute bronchial hyperreactivity were unaffected (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown previously that persistent activation of the Gs signaling pathway can augment muscarinic M 3 receptor-mediated inositol phosphate production 40 . At first glance, the results reported herein might appear to be in good accordance with this earlier report as we detected enhanced muscarinic M 3 receptor signaling in the presence of cAMP elevating agents such as CTX ( Fig.…”
Section: Dynamic Mass Redistribution Faithfully Reports Signaling Of mentioning
confidence: 97%